1984
DOI: 10.1136/adc.59.11.1034
|View full text |Cite
|
Sign up to set email alerts
|

Mycoplasma pneumoniae: acute illness, antibiotics, and subsequent pulmonary function.

Abstract: SUMMARY One hundred and eight children presenting with Mycoplasma pneumoniae infection were assessed during the acute illness and followed for three years. The incidence of wheezing with the acute infection (40%) was greater than expected in a normal childhood population. The initial illness precipitated wheezing for the first time in some subjects but others wheezed only with the acute illness. In non-asthmatic subjects significant bronchodilator responsiveness was present one month after infection. Children … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
41
0
1

Year Published

1989
1989
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(42 citation statements)
references
References 13 publications
0
41
0
1
Order By: Relevance
“…Lung abnormalities, including reduced pulmonary clearance and airway hyperresponsiveness, may persist for weeks to months after an infection with M. pneumoniae (227,279,295,359,377). Marc et al (279) reported abnormalities in pulmonary function tests in up to 50% of children, and Kim et al (227) described abnormal computerized axial tomography studies for 37% of children months to years after an episode of M. pneumoniae respiratory tract infection, thus establishing the ability of mycoplasmas to induce chronic and possibly permanent lung damage long after resolution of respiratory tract symptoms.…”
Section: Asthma and Other Chronic Lung Conditionsmentioning
confidence: 99%
“…Lung abnormalities, including reduced pulmonary clearance and airway hyperresponsiveness, may persist for weeks to months after an infection with M. pneumoniae (227,279,295,359,377). Marc et al (279) reported abnormalities in pulmonary function tests in up to 50% of children, and Kim et al (227) described abnormal computerized axial tomography studies for 37% of children months to years after an episode of M. pneumoniae respiratory tract infection, thus establishing the ability of mycoplasmas to induce chronic and possibly permanent lung damage long after resolution of respiratory tract symptoms.…”
Section: Asthma and Other Chronic Lung Conditionsmentioning
confidence: 99%
“…Agents Chemother., p. 700, 1999). Increased bronchoconstriction with acute infection and impaired pulmonary function, especially of small airways, for up to 3 years after initial infection has also been described (5,14,17,23,30; Esposito et al, 39th ICAAC). Recent investigations have suggested that timely and effective treatment of acute M. pneumoniae respiratory infection can improve the course of reactive airway disease beyond the acute episode of wheezing and can prevent the development of deleterious changes in pulmonary function tests (Esposito et al, 39th ICAAC; D. Gendrel, E. Marc, F. Moulin, et al, Abstr.…”
mentioning
confidence: 99%
“…Most of these agents are primarily bacteriostatic for M. pneumoniae, and only the fluoroquinolones have been shown to be bactericidal (10, 42). While M. pneumoniae can be cultured from respiratory secretions for long periods after acute infection even after appropriate antimicrobial therapy, most antibiotics produce satisfactory clinical results, with a significant reduction in the duration of symptoms compared with no treatment (30,36). Macrolide and related antibiotics are generally considered the therapy of choice for M. pneumoniae infections in children and adults.…”
mentioning
confidence: 99%